2023
DOI: 10.47175/rielsj.v4i1.608
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Blended Collaborative Learning on the English Reading Comprehension

Abstract: The aim of this research was to examine the impact of blended collaborative learning on Iranian learners’ understanding concept of English texts. Among the statistical population of eighth grade male students in Birjand in the academic year, 2021 which numbered 637 people, 30 students were purposefully separated into two experimental and control groups using the available sampling method. After taking the Oxford Placement Test and the purposeful appointment of learners in experimental and control groups, a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(14 reference statements)
0
0
0
Order By: Relevance
“…Similar to this current research, Khalil (2018) highlighted the advantage of Google Applications in establishing collaborative learning environment which supported teacher and student interactions. Interaction in online learning environments seeks to combine technology with traditional media and is not limited to an instrumental approach (Motlagh et al, 2023). It is important to note that interaction among peers is an essential factor in determining the success of collaborative learning (Lambropoulos & Pitsou, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to this current research, Khalil (2018) highlighted the advantage of Google Applications in establishing collaborative learning environment which supported teacher and student interactions. Interaction in online learning environments seeks to combine technology with traditional media and is not limited to an instrumental approach (Motlagh et al, 2023). It is important to note that interaction among peers is an essential factor in determining the success of collaborative learning (Lambropoulos & Pitsou, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In the context of teaching EFL, Motlagh et al (2023) revealed that blended collaborative learning contributed to better performance of students' English reading comprehension especially in terms of understanding the concept of English texts and using proper vocabulary to complete the texts. Butarbutar et al (2023) found that blended collaborative learning was successful to implement in teaching speaking English as a foreign language.…”
Section: Introductionmentioning
confidence: 99%